Reduced Retinal Microvascular Perfusion in Patients With Stroke Detected by Optical Coherence Tomography Angiography - Liu, Baoyi; Hu, Yijun; Ma, Guixian; Xiao, Yu; Zhang, Bin; Liang, Yingying; Zhong, Pingting; Zeng, Xiaomin; Lin, Zhanjie; Kong, Huiqian; Wu, Guanrong; Du, Zijing; et al. (Frontiers in Aging Neuroscience, 2021)
Currently, there is a short of biomarkers for stroke, one of the leading causes of death and disability in aging population. Retinal vessel offers a unique and accessible “window” to study the microvasculature in vivo. However, the relationship between retinal microvasculature and stroke is not entirely clear. To investigate the retinal microvascular characteristics in stroke, we recruited stroke patients and age-matched control subjects from a tertiary hospital of China. Macular vessel density (VD) in superficial capillary plexus (SCP) and deep capillary plexus (DCP), metrics of foveal avascular zone (FAZ) and optic disc VD measured by optical coherence tomography angiography (OCTA) were recorded for analysis. A total of 189 stroke patients and 195 control subjects were included. After adjusting for sex, visual acuity, systolic and diastolic blood pressure, history of smoking, levels of HbA1c, cholesterol and high-density lipoprotein, macular VD of SCP and DCP in all sectors was decreased in stroke patients. The VD around the FAZ and the VD of the optic disc were lower in the stroke group. Logistic regression found parafovea-superior-hemi VD of DCP > 54.53% (odds ratio: 0.169) as a protective factor of stroke. Using the integration of all OCTA parameters and traditional risk factors, the area under receiver operating characteristic curve of distinguishing stroke patients was 0.962, with the sensitivity of 0.944 and the specificity of 0.871. Our work demonstrates that retinal VD is decreased in stroke patients independently on traditional risk factors of stroke, which may shed light on stroke monitoring using retinal microvascular parameters.